Switching enzyme activity by a temperature responsive inhibitor modified polymer. Issue 16 (30th January 2020) - Rottke, Falko O.; Heyne, Marie-Victoria; Reinicke, Stefan
Abstract : A thermoresponsive NIPAAm-based polymer is combined with the selective acetylcholinesterase inhibitor tacrine in order to create a strict in sense on/off switch for enzyme activity. Abstract : A thermoresponsive NIPAAm-based polymer is combined with the selective acetylcholinesterase inhibitor tacrine in order to create a strict in sense on/off switch for enzymatic activity. This polymer–inhibitor conjugate inhibits AChE at room temperature and enables reactivation of AChE by heating above the cloud point of the conjugate.